Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1002/(sici)1520-670x(199607)9:1<11::aid-jtra2>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Dietary chromium effects on tissue chromium concentrations and chromium absorption in rats

Abstract: Chromium (Cr) absorption is low (<1%) and there is a need to find Cr compounds that are absorbed better than inorganic Cr salts. Therefore, the incorporation of nine different chromium (Cr) compounds on tissue Cr concentration of 6‐week male Wistar rats was investigated. Chromium compounds tested were Cr chloride (Cr chloride), Cr acetate (Cr acetate), Cr potassium sulfate (CrAlum), Cr trihistidine (Cr histidine), Cr triglycine (Cr glycine), Cr trinicotinic acid (CrNA), Cr dinicotinic acid dihistidine (CrNA‐HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(59 citation statements)
references
References 0 publications
5
49
1
2
Order By: Relevance
“…In this study, Cr contents in liver and kidney were significantly increased with the addition of Cr as CrNano in the dosage of from 150 ppb to 1200 ppb. This is consistent with Anderson et al(1996), who reported that there was an approximate doubling of kidney Cr concentration and roughly 50% increased liver Cr concentration with the supplementation of 300 ppb Cr as Cr picoliante in the diets of pigs. Their results from rats (Anderson et al, 1996) showed that increase in tissue Cr following Cr supplementation were greatest for the kidney, followed by the liver, with considerably smaller changes in the heart and skeletal muscle tissues.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, Cr contents in liver and kidney were significantly increased with the addition of Cr as CrNano in the dosage of from 150 ppb to 1200 ppb. This is consistent with Anderson et al(1996), who reported that there was an approximate doubling of kidney Cr concentration and roughly 50% increased liver Cr concentration with the supplementation of 300 ppb Cr as Cr picoliante in the diets of pigs. Their results from rats (Anderson et al, 1996) showed that increase in tissue Cr following Cr supplementation were greatest for the kidney, followed by the liver, with considerably smaller changes in the heart and skeletal muscle tissues.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies indicated that supplemental Cr had effects on Cr content in tissues, but the results varied (Chang and Mowat, 1992;Anderson et al, 1996). In this study, Cr contents in liver and kidney were significantly increased with the addition of Cr as CrNano in the dosage of from 150 ppb to 1200 ppb.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Dowiedziono m.in. braku konsekwencji zdrowotnych związanych z bioakumulacją dużych dawek pikolinianu chromu (Cr +3 ) u szczurów (6). Nie zauważono również efektów genotoksycznych po propionianie Cr (III) (94).…”
Section: Chrom W Badaniach Na Zwierzętach I Ludziachunclassified
“…Wykazano w badaniach na szczurach, że absorpcja Cr w formie nikotynianu i pikolinianu jest wyższa niż w formie chlorku (6). Podobną prawidłowość wykazano u ludzi, u których absorpcja Cr w formie chlorku była niższa względem pikolinianu i Cr podawanego w postaci drożdży.…”
Section: Toksykokinetykaunclassified